2009
DOI: 10.1144/1470-9236/08-092
|View full text |Cite
|
Sign up to set email alerts
|

Initial geological considerations before installing ground source heat pump systems

Abstract: The performance of an open or closed loop ground source heat pump system depends on local geological conditions. It is important these are determined as accurately as possible when designing a system in order to maximise efficiency and minimise installation costs.Factors that need to be considered are surface temperature, sub-surface temperatures down to 100 -200 m, thermal conductivities and diffusivities of the soil and rock layers, groundwater levels and flows and aquifer properties. In addition rock streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 22 publications
(14 reference statements)
2
52
0
3
Order By: Relevance
“…A series of tests on the transparent soil using a KD2Pro thermal needle probe indicated it had a thermal conductivity of 0.33 W Á m À1 Á k À1 for the density and saturation conditions tested. This is lower than typical values reported for soils in literature, in the region of 0.7-1.5 W Á m À1 Á k À1 for sand and clay, respectively (Busby et al 2009); nevertheless, it was still suitable to model thermo-dynamic problems.…”
Section: Calibration Of the Test Environmentmentioning
confidence: 58%
“…A series of tests on the transparent soil using a KD2Pro thermal needle probe indicated it had a thermal conductivity of 0.33 W Á m À1 Á k À1 for the density and saturation conditions tested. This is lower than typical values reported for soils in literature, in the region of 0.7-1.5 W Á m À1 Á k À1 for sand and clay, respectively (Busby et al 2009); nevertheless, it was still suitable to model thermo-dynamic problems.…”
Section: Calibration Of the Test Environmentmentioning
confidence: 58%
“…During the observation period, a minimum of 7. Moving down from the surface, the ground temperature decreases exponentially with depth, due to the high thermal inertia of the ground: T oscillations are quite completely dumped bgl and a phase shift can be observed between T air_surf and T ground [12,15,23,55]. The amplitude of the T waves is already reduced at 0.60 m depth (T ground ), reaching an average value of 7.9 • C, even if seasonal variations are still visible and shifted in time compared to T air_2m (Figure 3a).…”
Section: Metereological Variablesmentioning
confidence: 99%
“…In the T depth profiles two main behaviors are identified, typical of non-operating (i.e., 15 (Figure 5c). Once shutting down the heat pump on 28 November 2016, the non-operating behavior is completely recovered after one week ( 5 December 2016), while already after three days (1 December 2016 the temperature difference between 0.40 and 0.80 m depth is annihilated.…”
Section: Metereological Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ tests, such as thermal response tests [12,13] or laboratory measurements [14] are sometimes possible, but the values obtained may deliver only well-centered information or may not always (if not at all) be representative of in situ conditions at a larger scale. Such data are often scarce if not missing and authors often have to rely on standard calculation charts, values found in the literature, or simply default values implemented in standard software (e.g., [15][16][17][18]). In addition, the heterogeneity of the material properties and their potential anisotropy, which are difficult to detect with standard integration methods, make the problem more complex.…”
Section: Introductionmentioning
confidence: 99%